The Influence of External Service Quality and Satisfaction on Patient Loyalty in Surabaya Islamic Hospital - Puryanti Puryanti; Budhi Setianto; Agus Aan Adriansyah (Jurnal Ilmiah Kesehatan, 2023)
One of the most essential things in the success of a service besides the value of satisfaction is customer loyalty. Loyalty here is an indicator of how many customers want to promote our services without us asking, while repeated visits from customers make customers happy and proud to use our services. This study aimed to measure the value of Customer Satisfaction, Loyalty, and External Service Quality. This study used secondary data, totaling 356 patients who completed a customer satisfaction survey at Surabaya Islamic Hospital. This study showed that the characteristics of the patients at the Surabaya Islamic Hospital were particularly women aged <25 years with a BPJS patient guarantor who lived 5-10 km and had known the Surabaya Islamic Hospital for > 20 years, while in the external service quality customer assessment which included product, organizational image, safety, empathy, reliability, responsiveness at Surabaya Islamic Hospital was good and there was a relationship between External service quality and satisfaction significantly influence patient loyalty at Surabaya Islamic Hospital.